Addressing Literacy Skills of Adolescent Girls in a Juvenile Justice Facility: Using the Self-Regulated Strategy Development Instructional Approach to Improve Written Summaries. - Pitzel, Allyson; Sanders, Sara; Rollins, Lauren Hart; Hester, Olivia R.; Hackney, Aimee J.; Jolivette, Kristine (Behavioral Disorders, 2025)
Developing the ability to summarize written text is a critical literacy skill set for adolescent students with disabilities. Four female students at-risk for emotional and behavioral disorders in a U.S. juvenile justice facility were taught the TRAP+IDEAS mnemonic using the self-regulated strategy development (SRSD) instructional approach to improve written summaries. The researchers employed a nonconcurrent multiple baseline design. Three students completed the study with observed improvements in summary content and quality of their written summaries with two students maintaining their summary content and quality during two weeks of maintenance. The social validity of the intervention, limitations, and future directions are presented.